Penerapan Terapi Rendam Kaki Air Hangat Pada Ibu Hamil Resiko Preeklamsi Di Klinik Kasih Ibu Tahun 2023 - Meta Rosaulina (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
In (WHO) in advanced countries the prevalence of preeclampsia tiers from 6-7%. consistent with Riskesdas, the prevalence of preeclampsia in pregnant ladies in Indonesia is two.7%. The incidence of preeclampsia in Indonesia on my own is round 128,273/twelve months. elements for the prevalence of preeclampsia in pregnant ladies encompass age, occupation, parity, gestational age, records of excessive blood pressure, and education. to analyze the impact of foot soak remedy with warmness water at the risk of preeclampsia pregnant women at Kasih Ibu fitness center. this test makes use of quantitative studies facts types with the quasi test methode and the only corporation pretest- posttest design. The test population turn out to be all prenagent ladies who visited the kasih iu clinical institution, totaling 40 humans and a sample of forty respondents using a whole sampling teahnique. the scale methode used a questionnaire which turn out to be analyzed univariaty and bivariately wiht parist T-test evaluation. The consequences of the statistical take a look at confirmed that there has been an effect of soaking ft in warmth water on decreasing blood stress in prenagent ladies danger of preeclamsia with a P-rate of zero,000 < 0,05 the perception of this examine turn out to be of soaking in warmth water on decreasing blood stress a prenagent. Keywords : Preeclampsia, Warm Water, Pregnant Women